2005
DOI: 10.1523/jneurosci.4716-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation and Reconsolidation of Incentive Learning in the Amygdala

Abstract: Incentive learning is the process via which animals update changes in the value of rewards. Current evidence suggests that, for food rewards in rats, this learning process involves the amygdala. However, it remains unclear whether this learning undergoes protein synthesis-dependent consolidation and "reconsolidation" processes in the lateral and basal nuclei of amygdala. Accordingly, we examined this hypothesis by local infusion of protein-synthesis inhibitor after devaluation of a food reward induced by a shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 37 publications
(46 reference statements)
8
75
0
Order By: Relevance
“…The BLA is part of an integrated circuit of neural structures implicated in the formation and storage of CS-US associations (Everitt et al, 1999 and in the processing of emotional events in relation to environmental stimuli that guide motivated behavior (Cardinal et al, 2002). Our data add to the growing body of evidence that the BLA is also involved in the reconsolidation of fear, drug, and incentive memories (Nader et al, 2000;Lee et al, 2005Lee et al, , 2006Wang et al, 2005) and extend these findings to include aversive drug memories retrieved by presenting opiate withdrawal-paired CSs. Together, these studies provide critical information on how reexposure to pavlovian cues associated with both drug intake and drug withdrawal may influence instrumental behavior to render drug-seeking compulsive in abstinent addicts.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The BLA is part of an integrated circuit of neural structures implicated in the formation and storage of CS-US associations (Everitt et al, 1999 and in the processing of emotional events in relation to environmental stimuli that guide motivated behavior (Cardinal et al, 2002). Our data add to the growing body of evidence that the BLA is also involved in the reconsolidation of fear, drug, and incentive memories (Nader et al, 2000;Lee et al, 2005Lee et al, , 2006Wang et al, 2005) and extend these findings to include aversive drug memories retrieved by presenting opiate withdrawal-paired CSs. Together, these studies provide critical information on how reexposure to pavlovian cues associated with both drug intake and drug withdrawal may influence instrumental behavior to render drug-seeking compulsive in abstinent addicts.…”
Section: Discussionsupporting
confidence: 60%
“…There is good evidence to suggest that the BLA is involved in incentive learning (Everitt et al, 1999;Balleine et al, 2003) and consolidation of memory for changes in the incentive value of rewards (Salinas et al, 1993). Moreover, reconsolidation of incentive memory for different food outcomes is blocked by intra-BLA infusions of anisomycin (Wang et al, 2005), suggesting that incentive learning for natural rewards undergoes protein synthesis-dependent reconsolidation in the BLA. Future studies that examine this phenomenon with drug-related stimuli could provide important information as to how incentive learning for appetitive drug-associated stimuli controls compulsive drug-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, rats with pre- [2] but not post- [5] training BLA lesions continue to approach to the food source, suggesting impaired re-valuation. Analogous results have been obtained using instrumental conditioning protocols for which food is devalued by satiation [6,8,9]. The types of reinforcer variables manipulated in previous studies, however, are limited and it is not known whether the BLA supports adjustment of choice behavior following changes in reinforcer properties such as magnitude.…”
Section: Introductionmentioning
confidence: 61%
“…We expected normal acquisition of preference, since previous studies have shown that BLA lesions do not affect the acquisition of operant behavior [6]. Pre- [2,6,8,9], but not post-training [5] BLA lesions decrease behavioral changes after reinforcer devaluation. We therefore hypothesized that pre-training but not post-training BLA lesions would disrupt changes in choice behavior during another type of contingency change, reinforcer magnitude reversal.…”
Section: Introductionmentioning
confidence: 86%
“…However, this result is still important, as the ability to display sensitivity to outcome value depends upon intact incentive memory (Balleine and Dickinson 1991;Parkes and Balleine 2013). Incentive memories are known to undergo reconsolidation (Wang et al 2005) and their loss would theoretically diminish instrumental responding. As both saline and MK-801-injected rats display sensitivity to reward devaluation, and visually there appears to be no difference in the magnitude of this effect, incentive memory is likely intact following the intervention (or at least restored following reexposure to the outcome).…”
Section: Sensitivity To Outcome Valuementioning
confidence: 99%